2011
DOI: 10.2215/cjn.03780411
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Time-Varying Albumin and Phosphorus on Mortality in Incident Dialysis Patients

Abstract: SummaryBackground and objectives Hypoalbuminemia and hyperphosphatemia have been shown to be strong predictors of mortality in dialysis patients that might not be independent from each other. We prospectively investigated the relationship and interaction between serum albumin and phosphorus with all-cause mortality in an inception cohort of incident dialysis patients.Design, setting, participants, & measurements We followed 235 incident dialysis patients in a prospective single-center cohort study (INVOR study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
2
31
0
1
Order By: Relevance
“…A recent study in Austria noted statistical multiplicative interactions between time-varying phosphorus and albumin, in which time-varying factors were updated to the most recent values every 3 months 14. Here, we confirmed a statistical multiplicative interaction between time-averaged phosphorus concentration and GNRI on all-cause mortality.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent study in Austria noted statistical multiplicative interactions between time-varying phosphorus and albumin, in which time-varying factors were updated to the most recent values every 3 months 14. Here, we confirmed a statistical multiplicative interaction between time-averaged phosphorus concentration and GNRI on all-cause mortality.…”
Section: Discussionsupporting
confidence: 86%
“…As nutritional index and phosphorus concentration are linked and may change dramatically overtime, the interaction between time-dependent nutritional index and phosphorus concentration must be carefully considered when evaluating their separate and combined effects on mortality 14. Although the Geriatric Nutritional Risk Index (GNRI)15 was originally intended for use as a screening tool for predicting risk of morbidity and mortality in elderly patients, it has since been validated for use in whole haemodialysis patients 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…We have successfully applied one of these approaches in a prospective study on incident dialysis patients, which was very useful for the interpretation of an interaction effect: we observed a significant interaction between time-varying values of albumin and phosphorus on overall mortality in our cohort [13]: for high albumin values, increasing phosphorus concentrations were significantly associated with an increased mortality risk, whereas the beneficial effect of increasing albumin values was only observed for low phosphorus levels. We concluded that decisions about phosphoruslowering therapy should also take albumin values into account and epidemiological studies and guidelines should consider this interplay.…”
Section: Discussionmentioning
confidence: 97%
“…Binder patients may reflect those who were more likely to have a liberal diet and therefore improved nutritional status [8,9,16]. Conversely, dietary phosphorus restriction has been shown to be associated with poor nutritional status and greater mortality risk [8,9,39,40]. The lower risk for mortality seen in the phosphorus binder cohort remained significant even after controlling for albumin.…”
Section: Discussionmentioning
confidence: 99%